Synthesis and Characterization of a Fluorescent Dianthracenoindacene - Frederickson, Conerd K.; Barker, Joshua E.; Dressler, Justin J.; Zhou, Zheng; Hanks, Evan R.; Bard, Jeremy P.; Zakharov, Lev N.; Petrukhina, Marina A.; Haley, Michael M. (Synlett, 2018)
A freely soluble dianthracenoindacene derivative has been synthesized using an ‘inside-out’ Friedel–Crafts alkylation method and is the first fluorescent diacenoindacene reported. Linear fusion of the anthracenes is confirmed by X-ray diffraction studies on the neutral molecule as well as its dianion. Based on predictions from our previous studies, this is also the least antiaromatic diacenoindacene derivative yet to be prepared, which is reflected in its highly negative and irreversible reduction. With its paratropicity essentially eliminated, we posit that the molecule is no longer deactivated by a conical intersection, typical of antiaromatic molecules, and therefore fluorescence is restored. This follows the trend shown in the related dianthracenopentalenes, with the reappearance of fluorescence when the outer acene groups are extended to linearly-fused anthracene moieties.
Keywords: antiaromaticity; aromaticity; fluorescence; indacene; indenofluorene